2019
DOI: 10.1039/c8lc01370e
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent whole-blood imaging flow cytometry for simple, rapid, and cost-effective drug-susceptibility testing of leukemia

Abstract: The drug susceptibility of leukemia cells in whole blood is evaluated by using extreme-throughput imaging flow cytometry with deep learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…Currently, the world's fastest imaging flow cytometry is realised by microfluidics-based optofluidic time-stretch (OTS) microscopy [21][22][23], which achieves continuous image acquisition at an ultrahigh rate of 10 million to 1 billion fps. Even though the theoretical limit of OTS microscopy allows a maximum flow velocity of 60 m/s [23,24], images were captured at a flow velocity of about 10 m/s [9,25] due to the limitation of presently available microfluidic technology. By employing a horizontal connection, it contributes to reduced pressure drop to increase flow velocity and further utilise the potential of imaging flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the world's fastest imaging flow cytometry is realised by microfluidics-based optofluidic time-stretch (OTS) microscopy [21][22][23], which achieves continuous image acquisition at an ultrahigh rate of 10 million to 1 billion fps. Even though the theoretical limit of OTS microscopy allows a maximum flow velocity of 60 m/s [23,24], images were captured at a flow velocity of about 10 m/s [9,25] due to the limitation of presently available microfluidic technology. By employing a horizontal connection, it contributes to reduced pressure drop to increase flow velocity and further utilise the potential of imaging flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate image capturing by OTS microscopy, K562, a human chronic myelogenous leukemia cell line was used. K562 cells were purchased from the Japanese Collection of Research Bioresources Cell Bank (JCRB).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study reported a maximum throughput of 1 million cells/s at a flow velocity of 10 m/s using a glass‐PDMS‐glass hybrid microfluidic device. In order to demonstrate the capability of our developed OTS microscopy, it is important to show that the images obtained at an ultra‐high‐flow velocity have the same quality as those obtained at a lower flow velocity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most promising approaches is to employ machine learning and artificial intelligence to metabolize these unprecedent amount of data. Although traditional machine learning offers advanced data processing capabilities, the advent of its most important component, the deep learning, made possible to analyze massive unstructured data such as images, drug-target interactions and computational biology [16][17][18][19]. These AI-based techniques employ algorithms that learn without direct programming overcoming the limitation of human recognition boosting human knowledge in various fields.…”
Section: Introductionmentioning
confidence: 99%